Pendampingan Bimbingan Pranikah dengan Aspek Psikologis dan Agama di Lembaga KUA Kota Kediri dalam Mewujudkan Keluarga Maslahat - Mu’awanah; Nila Zaimatus Septiana; Sheila Fakhria (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
Marriage is an attempt to unite two people in one family and aims to achieve a sakinah, mawaddah, wa rahmah household life. This goal is achieved if the two people who enter into a marriage have the insight, readiness, and skills needed. To prepare for this, pre-marital counseling is needed which is carried out by the Office of Religious Affairs (KUA). However, in fact, premarital counseling is not running optimally. This article aims to explain efforts to improve pre-marital counseling to minimize divorce cases in Kediri. The method used is a qualitative method with data collection techniques in the form of interviews. Meanwhile, efforts to improve pre-marital counseling are carried out using seminars, lectures, and focused group discussion (FGD) methods. The result of this dedication is increased awareness and insight to improve the quality and quantity of pre-marital counseling, both the KUA and the bride and groom. The hope, divorce cases can be suppressed.